Efektivitas pembelajaran Bahasa Mandarin di era digital pandemia dalam meningkatkan kemampuan berbahasa mahasiswa - Monika, Monika; Rudiansyah, Rudiansyah (2021)
Mandarin is a foreign language. In a number of studies, Mandarin is the most difficult language to learn because it has more than 50,000 characters and there are 4 basic tones that have different meanings when spoken. Many students find it difficult to learn Mandarin. This is the background for the author to examine whether the digital era that is rapidly transforming during the pandemic can make it easier for students to improve their Mandarin language skills. The method used in this research is descriptive analysis method. The results of this study state that learning Mandarin during the pandemic is not effective because the learning method tends to be boring. The results of the descriptive analysis among students, 90% gave the opinion that learning Mandarin during the pandemic was not very effective, boring and difficult to catch the material delivered even though using translation and other assistive media. Many factors cause such as unstable signal, voice cut off and not having a cellphone or laptop.